Constructing a nanocage-based universal carrier for delivering TLR-activating nucleic acids to enhance antitumor immunotherapy. (October 2022) - Zhang, Baoli; Chen, Xuehui; Tang, Guoheng; Zhang, Ruofei; Li, Jingyun; Sun, Guoming; Yan, Xiyun; Fan, Kelong
Abstract: Toll-like receptors (TLRs) have recently emerged as one of the potential targets for immune activation. Therefore, TLR agonists have gotten much attention in the immunotherapy field, and have been proven effective in activating antigen-presenting cells ( e.g., dendritic cells) and extensively studied for immune adjuvants. However, the applications of TLR-activating nucleic acids are severely limited by their poor effectiveness and utilization in vivo . Herein, we rationally bioengineered the natural nanocage-like protein, human heavy chain ferritin (HFn), with a positively charged cavity to construct a series of HFn(+) mutants for the internal encapsulation of TLR-activating nucleic acids via electrostatic interaction. Through systematic screenings, we selected the optimal HFn(+) nanocarrier and identified its universal loading ability for different types of TLR-activating nucleic acids. Through in vitro and in vivo experiments, we found that HFn(+) nanocarrier has significantly improved the delivery efficiency of TLR-activating nucleic acids, achieving efficient cell uptake, specific lysosomal localization and enhanced immune activation. Moreover, by virtue of its cage-like spatial structure, TLR-activating nucleic acid loaded HFn(+) shows great potential in combination with the other existing immune strategies via externally modifying function modules. In this study, we conjugated photodynamic photosensitizer chlorin e6 (Ce6) on the external surface of the HFn(+) carrier as an immunogenic death (ICD) inducer. The results show that the HFn(+)-based all-in-one platform effectively synergized TLR agonist-mediated and ICD-mediated immune activation, as evidenced by inducing significantly systemic immune responses, antitumor abscopal effect, and anti-metastasis efficacy in vivo . In conclusion, this nanocage-based carrier is a convenient and universal vehicle to effectively deliver different TLR-activating nucleic acids in vivo and may serve as a novel strategy for the combination of antitumor immunotherapies. Graphical Abstract: ga1 Highlights: This work rationally designs the nanocage-based carrier with a positive cavity via bioengineering technology.. The nanocage-based carrier allows universal encapsulation of different types of TLR-activating nucleic acids. The nanocage-based carrier facilitates delivery efficiency of TLR-activating nucleic acids in vitro and in vivo . The nanocarrier is available to serve as an all-in-one immunotherapy platform to synergize the existing immune strategies.